Bahasa dan Kesantunan - Arman, Lidya (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Politeness, traditionally is governed by the norms of society are internalized in the context of the culture and local wisdom. The concept of modesty in the traditional language that it was time to